What drives national efficiency in sub-Saharan Africa - Danquah, M.; Ouattara, B. (Economic Modelling, 2015)
In this paper, we use stochastic frontier analysis to examine whether differences in the transfer and absorption of technology help to explain cross-country differences in national efficiency levels in sub-Saharan Africa over the period 1970-2010. We find that trade policy on openness, machinery imports, stock of R&D, landlockedness and quality of institutions play a significant and quantitatively important role in explaining the differences in efficiency scores in SSA. Human capital, however, has an insignificant effect on efficiency. © 2014 Elsevier B.V.
Keywords: National efficiency; Stochastic frontier model; Sub-Saharan Africa